Use of benzodiazepines and benzodiazepine‐related drugs in the Nordic countries between 2000 and 2020 - Højlund, Mikkel; Gudmundsson, Larus S.; Andersen, Jacob H.; Saastamoinen, Leena K.; Zoega, Helga; Skurtveit, Svetlana O.; Wastesson, Jonas W.; Hallas, Jesper; Pottegård, Anton (Basic & clinical pharmacology & toxicology, 2023)
Use of benzodiazepines (BZ) and related drugs is subject to considerable debate due to problems with dependency and adverse events. We aimed to describe and compare their use across the Nordic countries. Data on the use of clonazepam, BZ‐sedatives, BZ‐hypnotics, and benzodiazepine‐related drugs (BZRD) in adults (≥20 years) were obtained from nationwide registers in Denmark, Finland, Iceland, Norway, and Sweden, 2000–2020. Main measures were therapeutic intensity (TI:DDD/1000 inhabitants [inhab.]/day) and annual prevalence (users/1000 inhab./year). Overall, TI of BZ and related drugs decreased in all Nordic countries from 2004 to 2020. However, there were considerable differences between countries in TI. In 2020, the TI of BZ and related drugs ranged from 17 DDD/1000 inhab./day in Denmark to 93 DDD/1000 inhab./day in Iceland. BZRD accounted for 55–78% of BZ use in 2020, followed by BZ sedatives at 20–44%, BZ‐hypnotics at <1–5%, and clonazepam at <1–2%. Annual prevalence of BZ use increased with age in all countries, and the highest annual prevalence was observed among people ≥80 years. Overall, the use of BZ and related drugs has decreased in all Nordic countries from 2004 to 2020, however, with considerable differences in their use between countries. The highest prevalence was observed among the oldest age groups—despite warnings against their use in this population.